K-pop em Fortaleza: o consumo e a produção de dança cover por fãs da música pop sul-coreana - Macedo, Iago Fillipi Patrocínio (2022)
With the mass media being able to quickly reach people around the world, cultures and lifestyles of different origins also became within the reach of people, who began to consume these materials according to their tastes and preferences. Consequently, society was divided into countless groups, each one with their own styles and behaviors, formed from similar consumption patterns. The focus of this research is on K-pop (South Korean pop music) fans, those who, inspired by idols' music videos, started to organize themselves to learn K-pop songs’ choreographies and to participate in dance competitions. With this context in mind, the general objective was outlined: To analyze how Fortaleza’s youth consume K-pop and produce choreographic performances in the cover dance scene. Therefore, using the ethnographic method, the daily life of the female cover dance group Primadonna was observed in person and through social networks such as Whatsapp, YouTube, Instagram and TikTok. In addition, narrative interviews were carried out with the Primadonna’s girls. This experience took place in the period of the pandemic outbreak of coronavirus, which brought to this research a time frame with specifics that had not happened before in the cover dance scene. As a result, it can be seen that the consumption of K-pop happens mainly on-line (from applications such as YouTube and Spotify). It was found that the production of cover choreographies is more related to the study, interpretation, criticism and improvement on dancing than to the production of a mere imitation. It is also noted that people in cover dance take their performances seriously, as if it were a job, investing their time, money and effort. However, this practice does not always become an actual profession due to the little financial return arising from it. It is concluded that local K-pop cover groups usually bring new interpretations to the choreographies released, a fact that highlights the criticality and creativity of the fans. It is observed that public policies for youth are very important for the growth and maintenance of fans' dance practice in Fortaleza. Many groups would not exist if such policies were not enforced. This dissertation also managed to highlight the strong presence of favela’s youth in dance groups. However, more studies are needed in the area to understand the relation between favela and K-pop.